Graphene supported Co–Mo–P catalyst for efficient photocatalyzed hydrogen generation. (4th May 2016) - Guo, Yueping; Lu, Gongxuan
Abstract: In this work, graphene(GP) supported Co–Mo–P catalysts for H2 generation were prepared via an in-situ synthesis strategy with the help of photogenerated electrons. The transmission electron microscopy images (TEM) of the catalysts indicated that the elements of Co, Mo and P were distributed in a relatively homogeneous manner in the catalysts. The Co–Mo–P/GP catalyst exhibited high photocatalytic activity for hydrogen generation sensitized by Eosin Y (EY) under visible light. The Mo/(Co + Mo) molar ratio (χMo ) was varied in the catalyst to study the effect of Mo doping on the catalytic efficiency. The highest rate of the H2 generation was found to be as high as 33.3 mmol·h −1 ·gCo −1 when the χMo was 10%. The apparent quantum efficiency (AQE) of the reaction over the Mo doped catalyst under 430 nm irradiation was 52.6%, which was six times higher than that using the un-doped Co–P/GO catalyst. Highlights: The graphene supported Co–Mo–P catalysts were synthesized via the in situ synthesis strategy. The effect of Mo/(Co + Mo) molar ratio was studied. The highest H2 evolution rate 33.3 mmol·h −1 ·gCo −1 was achieved. The apparent quantum efficiency (AQE) was accomplished 52.6%.